A Capability Approach for Official German Poverty and Wealth Reports: Conceptual Background and First Empirical Results - Christian Arndt; Jürgen Volkert (Institut für Angewandte Wirtschaftsforschung (IAW), 2007)
The majority of the literature related to Amartya Sens Capability Approach (CA) has been devoted to questions of development and developing countries. In this paper, however, with a theoretical concept and first empirical results at hand, we shed some light on Sens argument that the CA is also relevant to wealthy countries (Sen, 1999, p. 6). First, we discuss the political background of CA applications in the case of Germany. Second, we sketch out a new analytical framework for the assessment of poverty and wealth in affluent countries in general from a CA perspective. Third, we show how this framework can be based on a corresponding set of feasible indicators and up-to-date representative information in the German Socio-Economic Panel Study (GSOEP). Finally, three selected empirical examples underline the resulting possibilities for analyses of gender inequalities, the unequal distribution of political participation and interdependencies between financial and nonfinancial issues of poverty and wealth within this integrative framework.
Keywords: 330; poverty; wealth; capabilities; Amartya Sen; affluent countries; poverty determinants; Armut; Reichtum; Messung; Disparitätsmaß; Deutschland; capability approach